Analysis of Textbook Quality and Its Impact on The Formation of Elementary School Children's Character: Analisis Kualitas Buku Ajar dan Dampaknya Terhadap Pembentukan Karakter Anak SD - Saputri, Rizka Sofyan; Subrata, Heru; Indarti, Titik (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to analyze the quality of textbooks and their impact on the character formation of elementary school children. The research method used is qualitative with a content analysis approach. Based on the results and discussion, the Indonesian language textbook for fourth grade elementary school students in Indonesia Merdeka Curriculum applies characters based on Lickona's perspective from all aspects, although not every chapter has each aspect of character based on Lickona's perspective. There are efforts to integrate character values into the textbook, although there is still room for further improvement in presenting character values consistently. Provides further explanation regarding the various character development values which are an integral part of the Independent Curriculum.